The Effect of Problem Based Learning Model on Critical Thinking Ability of Students on Additives and Addictive Substances Class VIII SMPN 12 Padang - Mesia Dewi Hasanah; Heffi Alberida; Yosi Laila Rahmi (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2018)
Implementation of Curriculum 2013 requires students to learn actively, independently, and critical thinking. Critical thinking is an activity through thinking about ideas related to concepts or problems. The efforts to improve critical thinking skills of learners can be done by using the appropriate learning model. One of the learning models that can be used to improve the ability of critical thinking is a problem-based learning model. This type of research is quasi experiment with randomized control-group pretest posttest design. The sample of this research choosed by used purposive sampling method. Class VIII6 as experimental class and class VIII4 as control class. Data of this research result are quantitative data of critical thinking ability. Data were analyzed by using t test. The results showed that the mean difference of posttest value with pretest value of critical thinking ability of experimental class learners is higher than control class. Hypothesis testing with t-test obtained tcalculate=2,94>ttable= 1,67, then H1 accepted. Based on these results the authors conclude that the implementation of problem-based learning model has a positive effect on the ability to think critically learners on the material additives and addictive substances.